2021
DOI: 10.1136/gutjnl-2021-324032
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriresistance to antibiotics in Europe in 2018 and its relationship to antibiotic consumption in the community

Abstract: ObjectiveOur aim was to prospectively assess the antibiotic resistance rates in Helicobacter pylori strains in Europe in 2018 and to study the link between antibiotic consumption in the community and H. pylori resistance levels in the different countries.DesignThe proportion of primary antibiotic resistance cases of H. pylori and their corresponding risk factors were investigated in 24 centres from 18 European countries according to a standardised protocol. Data on antibiotic consumption in the community were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
171
1
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(231 citation statements)
references
References 32 publications
(31 reference statements)
3
171
1
9
Order By: Relevance
“…One meta-analysis including 178 studies from 65 countries in World Health Organization Regions reported primary and secondary resistance rates to clarithromycin, metronidazole, and levofloxacin were ≥15% [21]. A prospective study investigated in 24 centers from 18 European countries reported that primary antibiotic resistance of H. pylori was 21.4% for clarithromycin, 15.8% for levofloxacin, and 38.9% for metronidazole, associated with the consumption in the community of macrolides and intermediate-acting macrolides [22]. One research covering 176 articles from 24 countries in the Asia-Pacific region showed primary H. pylori resistance rates were 17% for clarithromycin, 44% for metronidazole, 18% for levofloxacin, 3% for amoxicillin, and 4% for tetracycline [23].…”
Section: Challenges Of H Pylori Management and Recommended Detecting Strategymentioning
confidence: 99%
“…One meta-analysis including 178 studies from 65 countries in World Health Organization Regions reported primary and secondary resistance rates to clarithromycin, metronidazole, and levofloxacin were ≥15% [21]. A prospective study investigated in 24 centers from 18 European countries reported that primary antibiotic resistance of H. pylori was 21.4% for clarithromycin, 15.8% for levofloxacin, and 38.9% for metronidazole, associated with the consumption in the community of macrolides and intermediate-acting macrolides [22]. One research covering 176 articles from 24 countries in the Asia-Pacific region showed primary H. pylori resistance rates were 17% for clarithromycin, 44% for metronidazole, 18% for levofloxacin, 3% for amoxicillin, and 4% for tetracycline [23].…”
Section: Challenges Of H Pylori Management and Recommended Detecting Strategymentioning
confidence: 99%
“…As many experts point out, the frequency of overuse and inappropriate prescription of antibiotics in the treatment of bacterial infections throws a shadow on the possible future utilization of many of them [4,8,9,23]. This issue is of particular importance because over the last 20 years a rapid increase in antibiotic resistance of H. pylori has been observed, and a very limited array of antibiotics are left in the treatment of multidrugresistant strains of this bacterium [5,23]. Therefore, intensive search for new compounds displaying anti-H. pylori activity (as performed in this study) is of pivotal usability with regard to future treatment algorithms.…”
Section: Antibacterial Activity Against Planktonic Formsmentioning
confidence: 99%
“…Currently, the treatment of H. pylori has reached the point where the majority of traditional methods of its eradication have lost their effectiveness [3]. H. pylori antibiotic resistance is the main cause of these therapeutic failures and a major challenge for clinicians [5]. The latest data on H. pylori antibiotic resistance in Europe showed that the level of primary resistance of this bacterium was 21.8% for clarithromycin (CLR), 15.8% for levofloxacin (LEV), and 38.9% for metronidazole (MTZ) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary resistance rates for clarithromycin, metronidazole and levofloxacin are 15% or higher in nearly all WHO regions[ 3 ]. Recent data on H. pylori antimicrobial resistance in European countries revealed overall primary resistance rates of 21.4%, 15.8% and 38.9% for clarithromycin, levofloxacin and metronidazole, respectively[ 4 ]. As resistance rates vary from region to region[ 3 - 5 ], consensus guidelines[ 6 - 11 ] recommend that first-line treatment for H. pylori is based on primary resistance rates in a given population.…”
Section: Introductionmentioning
confidence: 99%